Determination of probiotic concept product consumption among people of ages 14-65 - Sökülmez Kaya, Pınar; Karakan, Tarkan; Sezgin, Serap; Aydin Avci, İlknur and Arusoğlu, Gülcan (Progress in Nutrition, 2016)
Aim: This study was planned in order to determine the level of knowledge and consumption of probiotic products featured on their status in adults aged 15-69 living in Samsun. Methods: A total of between 15-69 years, with 761 volunteers, applying the survey data was collected. All data were analyzed using the SPSS 13.0 package program recorded on the computer. Results: Consumption of the probiotic product is 59.5%. They are also on the recommendation of 8.2%, 14.6% due to digestive problems, she loves the taste of 34.9%, to protect the health of 35.1%, and 7.2% reported that they consume for other reasons. No consume the probiotic product is 40.5%. They are not like the taste of 25.6%, 32.8% find it expensive, there is not knowledge about probiotics of 41.6%. 250 participants who have health problems, in terms of distribution according to age in the use of probiotic products, showed an increase with age (p = 0.024). Gender, age and education level had no effect on the consumption of probiotic products (p> 0.05). There is a statistically significant relationship between the level of income or health problem and probiotic products consumption (p = 0.023; p = 0.015). Conclusion: 59.5% of the participants probiotics product is consume. Probiotic product consumption make a difference not statistically significant by level of education but it is considered a bit of a younger generation through education. Health problems of participants use probiotic products showed an increase with age.